Prolonged Fasting as a Cause of Deep Vein Thrombosis: A Case Report - Roberge, Guillaume; Samson, Carine; Le Gal, Grégoire; Calabrino, Anthony (TH Open, 2023)
Background Intermittent fasting is becoming more popular as health benefits are described in recent literature. Various forms of fasting exist, one of them involving a zero-calorie diet and drinking only water. However, the safety of water-only fasting is still not well established. We report a case of a man who developed a lower limb deep vein thrombosis at the end of a 2-week water-only fasting and characterized by an initial period of 5 days of no food and no water intake. We reviewed literature regarding potential links between fasting and venous thromboembolism (VTE).Clinical Approach We believe that fasting can induce important dehydration, leading to hypercoagulability and then contribute to the development of a venous thrombosis. The patient was treated with apixaban for 3 months as is recommended in patients with a provoked event caused by a transient risk factor. No thrombotic recurrence was observed during the 6-month follow-up.Conclusion The public needs to be aware of the potential life-threatening complications associated with important dehydration in the setting of medically unsupervised fasting, and these might include VTE. Whether a VTE with dehydration as the only identified risk factor should be approached as a low recurrence risk situation or not still needs to be clarified.
Keywords: fasting; thrombosis; venous thrombosis; dehydration; anticoagulation